Host-driven remodeling of rumen microbiota supports lactation metabolism in buffalo - Ding, Zixu; Xu, Yixue; Wang, Yan; Liu, Miaoer; Zhu, Peng; Cui, Kuiqing; Yang, Chunyan; Xu, Changlong; Feng, Tong; Liu, Qingyou (Frontiers in Microbiology, 2025)
IntroductionRumen microbiota and host metabolites play a key role in regulating ruminant production performance and physiological adaptation. However, the interplay between host physiological status and rumen microbial-metabolite dynamics across lactation stages in buffaloes remains unclear.MethodsThis study employed a multi-omics approach, integrating metagenomic and serum metabolomic analyses, to investigate microbial remodeling and metabolic adaptations in buffaloes during lactation and dry periods.ResultsMetagenomic analysis revealed increased abundances of Anaerovibrio, Succiniclasticum, and Methanobrevibacter_A during lactation, associated with lipid hydrolysis, propionate production, and methanogenesis, respectively. Glycoside hydrolase families GH2, GH3, GH5, and GH13 were enriched, indicating elevated carbohydrate degradation potential. In contrast, Butyrivibrio, Fibrobacter, and Eubacterium_Q were predominant during the dry period, contributing to fiber degradation and butyrate synthesis. Functional pathways related to niacin metabolism, bicarbonate reabsorption, and neuroactive ligand-receptor interaction were significantly upregulated during lactation. Metabolomic profiling identified lactation-enriched metabolites such as indole-3-methylacetate, D-maltose, and gluconic acid, correlating with immune and metabolic indicators (e.g., IgA, glucose, LDL). Conversely, dry period metabolites such as 1-methylhistidine and 5-hydroxyindoleacetic acid indicated physiological shifts toward tissue repair and stress mitigation.DiscussionThe integrative analysis revealed that host physiological demands during lactation coordinate rumen microbial restructuring to enhance triglyceride degradation, fatty acid biosynthesis, and energy mobilization, thereby supporting milk production. These findings provide novel insights into the host-driven microbiome-metabolite axis underlying lactation in buffaloes.